2008
DOI: 10.1136/ard.2008.094151
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis versus diabetes as a risk factor for cardiovascular disease: a cross-sectional study, the CARRÉ Investigation

Abstract: Objectives: Patients with rheumatoid arthritis (RA) have an increased cardiovascular risk, but the magnitude of this risk is not known precisely. A study was undertaken to investigate the associations between RA and type 2 diabetes (DM2), a well-established cardiovascular risk factor, on the one hand, and cardiovascular disease (CVD) on the other. Methods: The prevalence of CVD (coronary, cerebral and peripheral arterial disease) was determined in 353 randomly selected outpatients with RA (diagnosed between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
188
2
23

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(223 citation statements)
references
References 36 publications
10
188
2
23
Order By: Relevance
“…Rheumatoid arthritis (RA) is the most common systemic autoimmune disease and is associated with excessive cardiovascular mortality (1,2). There is a decrease of 10-15 years in life expectancy in these patients compared with that in the general population, particularly in patients with severe disease (3).…”
mentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is the most common systemic autoimmune disease and is associated with excessive cardiovascular mortality (1,2). There is a decrease of 10-15 years in life expectancy in these patients compared with that in the general population, particularly in patients with severe disease (3).…”
mentioning
confidence: 99%
“…Premature atherosclerosis has been observed during the course of different systemic inflammatory diseases, such as rheumatoid arthritis and systemic lupus erythematosus [7][8][9][10][11][12][13][14][15][16][17][18]. In these diseases, an increased prevalence of atherosclerosis and, consequently, increased cardiovascular morbidity and mortality has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Toms et al 73 have reported a lower prevalence of MS in elderly patients using MTX; on the other hand, a subanalysis of the CARRE Investigation has not confi rmed those fi ndings. 13 …”
Section: Metabolic Syndromementioning
confidence: 99%
“…5 Individuals diagnosed with RA have greater likelihood of having other diseases associated, such as those of autoimmune etiology, 6,7 and comorbidities, such as systemic arterial hypertension (SAH), dyslipidemia, and diabetes mellitus (DM). [8][9][10][11][12][13][14] The understanding and adequate management of the comorbidities of patients with RA are fundamental, because those diseases contribute to an increased cardiovascular risk and to the greater mortality observed in that group. 15 The present study aimed at elaborating recommendations for the diagnosis and management of comorbidities in patients with RA, emphasizing the most frequent conditions.…”
Section: Introductionmentioning
confidence: 99%